2020
DOI: 10.1111/ahe.12621
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic investigation of the lumbosacral plexus of the helmeted guinea fowl (Numida meleagris)

Abstract: The study was conducted for the determination of the main nerves of the lumbosacral plexus in the helmeted guineafowl. Five helmeted guineafowls were used. Fowls were anaesthetised and the a. carotis communis was cut for blood drainage. Body cavities were revealed and were fixated with 10% formaldehyde. Nerves forming the lumbosacral plexus were dissected and photographed. Results were named according to the Nomina Anatomica Avium. It was determined that the lumbosacral plexus forms by 8 synsacral ventral rami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In recent years, studies on dogs have been conducted on sperm cells (Yousef et al, 2022), vaccines (Esmaeili et al, 2021), intestinal parasites (Ola-Fadunsin et al, 2023), serum concentrations of hormones (Mosallanejad et al, 2021), and canine distemper virus (Mohtahedzade et al, 2023). In previous studies, it was observed that the plexus lumbosacralis was studied in species such as Van cat (Nur et al, 2021), fox (De Carvalho Barros et al, 2019), Baladi breed dog (El-Gendy et al, 2021), sparrowhawk (Balkaya & Ozudogru, 2016), merlin (Akalan et al, 2019), puma (Londoño-Osorio et al, 2020, and helmeted guineafowl (Nilgun & Ismail, 2021). However, no study has been done on plexus lumbosacralis in Aksaray Malaklı breed dogs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies on dogs have been conducted on sperm cells (Yousef et al, 2022), vaccines (Esmaeili et al, 2021), intestinal parasites (Ola-Fadunsin et al, 2023), serum concentrations of hormones (Mosallanejad et al, 2021), and canine distemper virus (Mohtahedzade et al, 2023). In previous studies, it was observed that the plexus lumbosacralis was studied in species such as Van cat (Nur et al, 2021), fox (De Carvalho Barros et al, 2019), Baladi breed dog (El-Gendy et al, 2021), sparrowhawk (Balkaya & Ozudogru, 2016), merlin (Akalan et al, 2019), puma (Londoño-Osorio et al, 2020, and helmeted guineafowl (Nilgun & Ismail, 2021). However, no study has been done on plexus lumbosacralis in Aksaray Malaklı breed dogs.…”
Section: Introductionmentioning
confidence: 99%